Improving Knowledge of Community Health Worker about Stunting’s Prevention Through Structured Training Program in Malang - Hasanah, Zumroh; Kinanti, Rias Gesang; Puriastuti, Alifia Candra; Ratna, Ardhiyanti Puspita; Novembriani, Rizqie Putri (Global Health Science Group, 2024)
Background: Stunting is a significant public health issue in Indonesia. Improving the knowledge of community health workers, particularly health cadres, is crucial for effective stunting prevention in Indonesia. Objective: This study aims to analyze the effectiveness of structured training program about stunting prevention among health cadres in Sumberpasir Village, Pakis District, Malang Regency Method: This study employed a one-group pretest-posttest design. A total of 28 health cadres were recruited using a purposive sampling method. Data were collected using a validated questionnaire to assess stunting prevention knowledge. The intervention consisted of a 10-hour structured training program led by the expert (divided into five sessions, with 2.5 hours in each session). Data were analyzed using SPSS version 26. Given the non-parametric nature of the data, the Wilcoxon signed-rank test was used to compare the pretest and posttest scores. Results: The structured training program had a significant positive impact on the participants' knowledge. Conclusions: The knowledge and empowerment of health cadres are fundamental to the success of stunting prevention strategies in Indonesia. By enhancing their training, providing ongoing support, and fostering community engagement, health cadres can play a transformative role in reducing stunting rates among children.